Negative electrode, method of forming same, and rechargeable lithium battery

By using a dry negative electrode active material layer including crystalline carbon core, non-conductive layer and polytetrafluoroethylene binder in the negative electrode of the rechargeable lithium battery, the problem of initial efficiency reduction caused by the reaction between electrons and lithium is solved, and the problem of achieving the Efficient, simple drying process and high capacity effect.

CN119495703APending Publication Date: 2025-02-21SAMSUNG SDI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410652334.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-21
Filing Date
2024-05-24
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

During the charging and discharging process of the negative electrode of the existing rechargeable lithium battery, the reaction of electrons with lithium leads to a decrease in the initial efficiency, and it is difficult to take into account the simplicity of the drying process and the high capacity.

Method used

A negative electrode including a negative current collector and a dry negative electrode active material layer is used. The dry negative electrode active material layer consists of crystalline carbon cores, coated non-conductive layer and polytetrafluoroethylene binder. The non-conductive layer prevents crystalline carbon cores and poly The tetrafluoroethylene binder contacts directly, inhibiting electron movement.

Benefits of technology

The movement of electrons from the crystalline carbon core to the polytetrafluoroethylene binder is effectively inhibited, and the reaction between lithium and polytetrafluoroethylene is reduced, thereby improving the initial efficiency and taking into account the simplicity of the dry process and the high capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495703A_ABST
    Figure CN119495703A_ABST
Patent Text Reader

Abstract

The invention relates to a negative electrode, a method of forming the same, and a rechargeable lithium battery. The negative electrode for a rechargeable lithium battery includes a negative electrode current collector and a dry negative electrode active material layer on the negative electrode current collector, the dry negative electrode active material layer including: a negative electrode active material having a crystalline carbon core and a non-conductive layer coated on a surface of the crystalline carbon core; and a polytetrafluoroethylene binder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Embodiments of the present disclosure relate to a negative electrode for a rechargeable lithium battery and a rechargeable lithium battery including the same. Background Art

[0002] Rechargeable lithium batteries show excellent discharge voltage and high energy density. Electrodes for rechargeable lithium batteries can be prepared by a wet process or a dry process, and among these, research is being conducted on the dry process, which is a simpler process and provides higher capacity. Summary of the invention

[0003] One or more embodiments provide a negative electrode for a rechargeable lithium battery, comprising a negative electrode current collector and a dry negative electrode active material layer located on the negative electrode current collector, the dry negative electrode active material layer comprising: a negative electrode active material having a crystalline carbon core and a non-conductive layer coated on a surface of the crystalline carbon core; and a polytetrafluoroethylene binder.

[0004] The non-conductive layer may include a non-conductive polymer selected from polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, or a combination thereof.

[0005] The polytetrafluoroethylene binder may include fibrillated polytetrafluoroethylene.

[0006] The non-conductive layer may have a thickness of about 1 nm to about 10 nm.

[0007] The amount of the non-conductive layer may be about 0.1 wt % to about 2.0 wt % based on 100 wt % of the negative active material.

[0008] The amount of the polytetrafluoroethylene binder may be about 0.5 wt % to about 3.0 wt % based on 100 wt % of the dry negative active material layer.

[0009] The negative active material may be prepared by coating a non-conductive polymer liquid containing a non-conductive polymer in a solvent on a crystalline carbon core and drying the non-conductive polymer liquid.

[0010] One or more embodiments provide a rechargeable lithium battery, which includes a positive electrode, a non-aqueous electrolyte, and a negative electrode, the negative electrode including a negative electrode collector and a dry negative electrode active material layer located on the negative electrode collector, the dry negative electrode active material layer including: a negative electrode active material having a crystalline carbon core and a non-conductive layer coated on the surface of the crystalline carbon core; and a polytetrafluoroethylene binder.

[0011] When evolving gas analysis of a negative electrode is performed after a rechargeable lithium battery is subjected to formation charge and discharge, a height ratio of a peak associated with polytetrafluoroethylene appearing at about 500° C. to about 600° C. and a peak associated with a non-conductive polymer appearing at about 400° C. to about 500° C. of the rechargeable lithium battery may be about 2:1 to about 20:1.

[0012] When evolving gas analysis of a negative electrode is performed after a rechargeable lithium battery is subjected to formation charge and discharge, a height ratio of a peak associated with polytetrafluoroethylene appearing at about 500° C. to about 600° C. and a peak associated with a non-conductive polymer appearing at about 400° C. to about 500° C. of the rechargeable lithium battery may be about 5:1 to about 20:1.

[0013] One or more embodiments provide a method for forming a negative electrode for a rechargeable lithium battery, which includes forming a negative electrode current collector and forming a dry negative electrode active material layer on the negative electrode current collector, the dry negative electrode active material layer including: a negative electrode active material having a crystalline carbon core and a non-conductive layer coated on the surface of the crystalline carbon core; and a polytetrafluoroethylene binder.

[0014] Forming the negative active material may include adding a non-conductive polymer to a solvent to form a non-conductive polymer liquid, coating the non-conductive polymer liquid on a crystalline carbon core, and drying the non-conductive polymer liquid on the crystalline carbon core to form the negative active material. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Features will become apparent to those skilled in the art by describing exemplary embodiments in detail with reference to the accompanying drawings, in which:

[0016] Figure 1 is a schematic diagram illustrating a rechargeable lithium battery according to one or more embodiments.

[0017] Figure 2 Graphs showing thermogravimetric analysis and evolved gas analysis of the negative electrode active material of Comparative Example 2 before formation charge and discharge.

[0018] Figure 3 Graphs showing thermogravimetric analysis and evolved gas analysis of the negative electrode active material of Example 1 after formation charge and discharge.

[0019] Figure 4 Graphs showing thermogravimetric analysis and evolved gas analysis of the negative electrode active material of Comparative Example 1 after formation charge and discharge.

[0020] Figure 5 The graphs are thermogravimetric analysis and evolved gas analysis of the negative electrode active material of Comparative Example 2 after formation charge and discharge.

[0021] Figure 6 Graphs showing the charge and discharge characteristics of Example 1 and Comparative Examples 1 and 2. DETAILED DESCRIPTION

[0022] Example embodiments will now be described more fully hereinafter with reference to the accompanying drawings; however, they may be implemented in different forms and should not be construed as limited to the embodiments set forth herein. Rather, these embodiments are provided so that this disclosure will be thorough and complete, and will convey exemplary implementations to those skilled in the art.

[0023] In the drawings, the dimensions of layers and regions may be exaggerated for clarity of illustration. It will also be understood that when a layer or element is referred to as being "on" or "over" another layer or substrate, it can be directly "on" or "over" the other layer or substrate, or there may be intervening layers. Additionally, it will be understood that when a layer is referred to as being "between" two layers, it can be the only layer between the two layers, or there may be one or more intervening layers. Like reference numerals refer to like elements throughout.

[0024] In this document, singular expressions include plural expressions unless the context clearly indicates otherwise. The term "combination thereof" may include mixtures, laminates, complexes, copolymers, alloys, blends, reactants of components, etc. The terms "comprise", "include" or "have" are intended to indicate the presence of the performed features, quantities, steps, constituent elements, or combinations thereof, but it should be understood that the possibility of the presence or addition of one or more other features, quantities, steps, constituent elements, or combinations thereof is not precluded.

[0025] In addition, herein, the "layer" includes a shape formed entirely on the entire surface or a shape formed on a part of the surface when viewed from a plan view.

[0026] In this document, "or" is not interpreted as an exclusive meaning. For example, "A or B" is interpreted to include A, B, A+B, etc.

[0027] Unless otherwise defined in the specification, the particle size or particle size may be an average particle size (D50). The average particle size (D50) indicates the average particle size at which the cumulative volume is 50% by volume in the particle size distribution. The particle size may be measured by methods well known to those skilled in the art (e.g., by a particle size analyzer, by a transmission electron microscope image or a scanning electron microscope image). Alternatively, a dynamic light scattering measurement device may be used to perform data analysis, and the number of particles in each particle size range may be counted, whereby the average particle size (D50) value may be easily obtained by calculation.

[0028] According to example embodiments, a negative electrode for a rechargeable lithium battery may include a negative electrode current collector and a dry negative electrode active material layer located on the negative electrode current collector. The dry negative electrode active material layer may include: a negative electrode active material having a crystalline carbon core and a non-conductive layer coated on the surface of the crystalline carbon core; and a polytetrafluoroethylene binder. Such a negative electrode refers to a negative electrode prepared by a dry process without using a solvent in the preparation of the negative electrode active material, rather than a negative electrode prepared by a wet process.

[0029] In the negative active material according to one or more embodiments, the non-conductive layer coated on the crystalline carbon core can prevent direct contact between the crystalline carbon core and the polytetrafluoroethylene binder. This can inhibit the movement of electrons from the crystalline carbon core to the polytetrafluoroethylene binder, thereby effectively inhibiting the reduction in initial efficiency caused by the electrons moving to the polytetrafluoroethylene binder reacting with lithium to generate LiF and reversibly consuming lithium during charging and discharging.

[0030] If the crystalline carbon core is substantially completely covered by the non-conductive layer, the effect due to the formation of the non-conductive layer can be achieved, whereas if the crystalline carbon core is only partially covered by the non-conductive layer or if the crystalline carbon is physically mixed with the polymer constituting the non-conductive layer, this effect cannot be obtained.

[0031] The non-conductive layer may include a polymer, for example, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, or a combination thereof.

[0032] In one or more embodiments, the thickness of the non-conductive layer may be about 1 nm to about 10 nm, for example, about 2 nm to about 8 nm or about 3 nm to about 6 nm. If the thickness of the non-conductive layer is within the above range, the embedding and de-embedding of lithium ions in the crystalline carbon can be well maintained, and the movement of electrons from the crystalline carbon core to the polytetrafluoroethylene binder can be more effectively suppressed.

[0033] In some embodiments, the thickness of the non-conductive layer may be measured by a SEM image or a TEM image, but is not limited thereto, and thus, may be measured by any technique as long as the thickness of the non-conductive layer is measured.

[0034] In one or more embodiments, based on 100wt% of the negative electrode active material, the amount of the non-conductive layer may be about 0.1wt% to about 2.0wt%, for example, about 0.2wt% to about 1.5wt% or about 0.3wt% to about 0.9wt%. If the amount of the non-conductive layer is within the above range, the capacity of the negative electrode may not be reduced and the movement of electrons from the crystalline carbon core to the polytetrafluoroethylene binder may be more effectively suppressed. For example, the amount of the non-conductive layer can be measured by thermogravimetric analysis (TGA).

[0035] The crystalline carbon may have any suitable shape. For example, the crystalline carbon may be of non-specific shape or may be in the form of flakes, scales, spheres, fibers (eg, fibrous natural graphite or artificial graphite), or a combination thereof.

[0036] In the negative electrode of one or more embodiments, the polytetrafluoroethylene binder may include fibrillated polytetrafluoroethylene. If a shear force is applied, the polytetrafluoroethylene binder may be transformed into a fibrous state, for example, fibrillated, so that the polytetrafluoroethylene binder is mixed with a negative active material and a shear force is applied thereto, thereby entangled with the fibrillated polytetrafluoroethylene binder and the negative active material to prepare a negative active material layer, making it possible to prepare a dry negative electrode.

[0037] Based on 100 wt % of the dry negative active material layer, the amount of the polytetrafluoroethylene binder may be about 0.5 wt % to about 3.0 wt %, for example, about 0.6 wt % to about 2.6 wt % or about 0.8 wt % to about 2.4 wt %. If the amount of the polytetrafluoroethylene binder is within the above range, the dry negative active material layer can be more efficiently prepared.

[0038] The dry negative electrode active material layer may optionally further include a conductive material. In the case where a conductive material is further included in the dry negative electrode active material layer, the amount of the negative electrode active material may be about 94 wt % to about 99 wt %, for example, about 96 wt % to about 99 wt %, based on 100 wt % of the dry negative electrode active material layer, the amount of the polytetrafluoroethylene binder may be about 0.5 wt % to about 3 wt %, for example, about 0.5 wt % to about 2 wt %, and the amount of the conductive material may be about 0.5 wt % to about 3 wt %, for example, about 0.5 wt % to about 2 wt %.

[0039] A conductive material may be included to provide electrode conductivity, and any conductive material may be used as the conductive material unless it causes a chemical change. Examples of the conductive material may include: a carbon-based material, such as natural graphite, artificial graphite, carbon black, carbon fiber, acetylene black, Ketjen black, etc.; a metal-based material of a metal powder or metal fiber, which includes, for example, copper, nickel, aluminum, silver, etc.; a conductive polymer, such as a polyphenylene derivative; or a mixture thereof. The carbon black may be, for example, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, or a combination thereof.

[0040] The negative electrode current collector may include one selected from, for example, copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and a combination thereof.

[0041] <Preparation of Negative Electrode>

[0042] In the negative electrode according to one or more embodiments, a negative active material may be first prepared.

[0043] The negative electrode active material can be prepared by adding a non-conductive polymer to a solvent to prepare a non-conductive polymer liquid, and coating the non-conductive polymer liquid on the crystalline carbon core. As such, the crystalline carbon core is coated with the non-conductive polymer liquid so that the non-conductive layer can be present so as to substantially, completely and continuously surround the surface of the crystalline carbon core in the form of a layer, and as a result, the surface of the crystalline carbon core is not exposed to the outside.

[0044] The non-conductive polymer may be, for example, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, or a combination thereof. The solvent may be water or an organic solvent, and the organic solvent may be, for example, N-methylpyrrolidone, etc. However, the solvent may be any appropriate solvent as long as it can dissolve the non-conductive polymer.

[0045] In the non-conductive polymer liquid, the amount of solid may be about 0.5 wt % to about 10.0 wt %, for example, about 1.0 wt % to about 8.0 wt % or about 4.0 wt % to about 6.0 wt %, based on 100 wt % of the non-conductive polymer liquid.

[0046] The coating process may be performed by a liquid coating process, for example, a dipping process, a spraying process, or the like.

[0047] The negative electrode active material prepared by the above process and the polytetrafluoroethylene binder and the optional conductive material are dry mixed. The resulting mixture is extruded to prepare the negative electrode active material layer. Dry mixing refers to a process without using a solvent. The dry mixing can be performed at a speed of about 1000 rpm to about 10000 rpm, for example, about 1500 rpm to about 8000 rpm or about 2000 rpm to about 7000 rpm, and can be performed for about 1 minute to about 30 minutes. During the dry mixing, the polytetrafluoroethylene binder can be fibrillated.

[0048] The negative electrode active material layer may be a sheet type and may be a self-standing film. The negative electrode active material layer may be bonded to a negative electrode current collector (eg, coated on a negative electrode current collector) to prepare a negative electrode. The bonding process may be, for example, a lamination process.

[0049] <Rechargeable lithium battery>

[0050] The rechargeable lithium battery may include a negative electrode, a positive electrode, and a non-aqueous electrolyte. In one or more embodiments, after the rechargeable lithium battery is subjected to formation charge and discharge, if the evolved gas analysis (EGA) of the negative electrode is analyzed, the peak associated with polytetrafluoroethylene appearing at about 500°C to about 600°C and the peak associated with the non-conductive polymer appearing at about 400°C to about 500°C may have a height ratio of about 2:1 to about 20:1, for example, about 5:1 to about 20:1 or about 8:1 to about 15:1. After formation charge and discharge, if the measurement result of the EGA of the negative electrode meets the above conditions, it indicates that polytetrafluoroethylene does not react with lithium ions and remains in the negative active material layer even after formation charge and discharge. It can be understood from these results that the non-conductive layer coated on the surface of the crystalline carbon core can prevent or substantially minimize the transfer of lithium ions from the crystalline carbon core to the polytetrafluoroethylene binder, and therefore, the reaction between polytetrafluoroethylene and lithium can be suppressed.

[0051] If the non-conductive layer is not present on the surface of the crystalline carbon core, ions may be transferred from the crystalline carbon core to the polytetrafluoroethylene binder during formation charge and discharge, and as a result, react with lithium ions to form LiF, thereby reducing polytetrafluoroethylene. In this case, if EGA of the negative electrode is performed, the height ratio of the peak associated with polytetrafluoroethylene appearing at about 500° C. to about 600° C. and the peak associated with the non-conductive polymer appearing at about 400° C. to about 500° C. may be about 1:1.

[0052] The formation charge and discharge may be performed by cycling charge and discharge at about 0.1C to about 1C once to three times.

[0053] <Positive Electrode>

[0054] The positive electrode may include a positive current collector and a positive active material layer formed on the positive current collector. The positive active material may include a lithiated intercalation compound that reversibly intercalates and deintercalates lithium ions. In other embodiments, one or more composite oxides of a metal selected from, for example, cobalt, manganese, nickel, and combinations thereof and lithium may be used. In some embodiments, a compound represented by one of the following chemical formulas may be used: Li a A 1-b X b D 1 2(0.90≤a≤1.8, 0≤b≤0.5); Li a A 1- b X b O 2-c1 D 1 c1 (0.90≤a≤1.8, 0≤b≤0.5, 0≤c1≤0.05); Li a E 1-b Xb O 2-c1 D 1 c1 (0.90≤a≤1.8,0≤b≤0.5,0≤c1≤0.05);Li a HAVE BEEN 2-b X b O 4-c1 D 1 c1 (0.90≤a≤1.8,0≤b≤0.5,0≤c1≤0.05);Li a Ni 1-b-c Co b X c D 1 α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α≤2);Li a Ni 1-b-c Co b X c O 2-α T α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α<2);Li a Ni 1-b-c Co b X c O 2-α T2(0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α<2);Li a Ni 1-b-c Mr b X c D 1 α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α≤2);Li a Ni 1-b-c Mr b X c O 2-α T α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α<2);Li a Ni 1-b-c Mr b X c O 2-α T2(0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α<2);Li a Ni b HAVE BEEN c G dO2(0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0.001≤d≤0.1); Li a Ni b Co c L 1 d G e O2 (0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, 0≤e≤0.1); Li a NeG b O2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a CoG b O2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn 1-b G b O2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn b O4(0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn 1-g G g PO4(0.90≤a≤1.8, 0≤g≤0.5); QO2; QS2; LiQS2; V2O5; LiV2O5; LiZO2; LiNiVO4; Li (3-f) J2(PO4)3(0≤f≤2);Li (3-f) Fe2(PO4)3(0≤f≤2);Li a FePO4(0.90≤a≤1.8).

[0055] In the above chemical formula, A is selected from Ni, Co, Mn or a combination thereof; X is selected from Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, rare earth elements or a combination thereof; D 1 is selected from O, F, S, P or a combination thereof; E is selected from Co, Mn or a combination thereof; T is selected from F, S, P or a combination thereof; G is selected from Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V or a combination thereof; Q is selected from Ti, Mo, Mn or a combination thereof; Z is selected from Cr, V, Fe, Sc, Y or a combination thereof; J is selected from V, Cr, Mn, Co, Ni, Cu or a combination thereof; and L 1 Selected from Mn, Al or a combination thereof.

[0056] These compounds may have a coating on the surface, or may be mixed with another compound having a coating. The coating may include at least one coating element compound selected from an oxide of a coating element, a hydroxide of a coating element, an oxyhydroxide of a coating element, an oxycarbonate of a coating element, or a hydroxycarbonate of a coating element. The compound used for the coating may be amorphous or crystalline. The coating elements included in the coating may include Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a mixture thereof. The coating may be provided by using these elements in a compound in a manner that has no adverse effect on the characteristics of the positive active material. For example, the method may include any coating method, such as spraying, dipping, etc., but since it is well known in the relevant art, it is not explained in more detail.

[0057] In the positive electrode, the amount of the positive active material may be about 90 wt % to about 98 wt % based on the total weight of the positive active material layer.

[0058] In some embodiments, the positive electrode active material layer may further include a binder and a conductive material, and the binder and the conductive material may each be included in an amount of about 1 wt % to about 5 wt % based on the total amount of the positive electrode active material layer.

[0059] The binder improves the bonding properties between the positive electrode active material particles and the bonding properties between the positive electrode active material particles and the positive electrode current collector. Examples thereof include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc.

[0060] A conductive material is included to provide electrode conductivity. Any conductive material can be used as the conductive material unless it causes a chemical change. Examples of the conductive material may include: a carbon-based material, such as natural graphite, artificial graphite, carbon black, carbon fiber, acetylene black, Ketjen black, etc.; a metal-based material of a metal powder or metal fiber, which includes, for example, copper, nickel, aluminum, silver, etc.; a conductive polymer, such as a polyphenylene derivative; or a mixture thereof.

[0061] The positive electrode current collector may include, for example, Al.

[0062] The positive electrode can be prepared by mixing a positive active material, a binder and a conductive material in a solvent to prepare a positive active material composition, and coating the positive active material composition on a positive current collector. The solvent may be, for example, N-methylpyrrolidone.

[0063] <Non-aqueous electrolyte>

[0064] The non-aqueous electrolyte includes a non-aqueous organic solvent and a lithium salt.

[0065] The nonaqueous organic solvent serves as a medium for transporting ions participating in the electrochemical reaction of the battery.

[0066] The non-aqueous organic solvent may include carbonate solvents, ester solvents, ether solvents, ketone solvents, alcohol solvents or aprotic solvents. Carbonate solvents may include, for example, dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. Ester solvents may include, for example, methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, mevalonolactone, caprolactone, etc. Ether solvents may include, for example, dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc. Ketone solvents may include, for example, cyclohexanone, etc. Alcohol solvents may include, for example, ethanol, isopropanol, etc. Aprotic solvents may include, for example, nitrile (e.g., R-CN (wherein R is a C2-C20 straight chain, branched chain or cyclic hydrocarbon group, and may include a double bond, an aromatic ring or an ether bond)), amide (e.g., dimethylformamide), dioxolane (e.g., 1,3-dioxolane, 1,4-dioxolane, etc.), sulfolane, etc.

[0067] The non-aqueous organic solvent may include a phosphorus-based solvent, for example, trimethyl phosphate, triethyl phosphate, triphenyl phosphate, tris(2,2,2-trifluoroethyl)phosphate, tris(2,2,2-trifluoroethyl)phosphite, or a combination thereof, and may include a sulfone-based solvent, for example, dimethyl sulfone, ethyl methyl sulfone, or a combination thereof.

[0068] The nonaqueous organic solvent may be used alone or in a mixture. If the nonaqueous organic solvent is used in a mixture, the mixing ratio may be controlled according to desired battery performance, and this may be well known to those skilled in the relevant art.

[0069] If the non-aqueous organic solvent is used as a mixture, a mixed solvent of a cyclic carbonate and a linear carbonate, a mixed solvent of a cyclic carbonate and a propionate solvent, or a mixed solvent of a cyclic carbonate, a linear carbonate and a propionate solvent can be used. The propionate solvent can be, for example, methyl propionate, ethyl propionate, propyl propionate or a combination thereof.

[0070] Herein, if a cyclic carbonate and a chain carbonate or a cyclic carbonate and a propionate solvent are mixed, they can be mixed in a volume ratio of about 1:1 to about 1:9, and thus, the performance of the non-aqueous electrolyte can be improved. In addition, if a cyclic carbonate, a chain carbonate and a propionate solvent are mixed, they can be mixed in a volume ratio of about 1:1:1 to about 3:3:4. The mixing ratio of the solvent can be appropriately adjusted according to the desired characteristics.

[0071] The nonaqueous organic solvent may further include an aromatic hydrocarbon solvent in addition to the carbonate-based solvent. The carbonate-based solvent and the aromatic hydrocarbon solvent may be mixed together in a volume ratio of about 1:1 to about 30:1.

[0072] The aromatic hydrocarbon organic solvent may be an aromatic hydrocarbon compound represented by Chemical Formula 1.

[0073] [Chemical formula 1]

[0074]

[0075] In Chemical Formula 1, R1 to R6 are the same or different and are selected from hydrogen, halogen, C1 to C10 alkyl, C1 to C10 halogenated alkyl, and combinations thereof.

[0076] Specific examples of aromatic hydrocarbon organic solvents may be selected from benzene, fluorobenzene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, chlorobenzene, 1,2-dichlorobenzene, 1,3-dichlorobenzene, 1,4-dichlorobenzene, 1,2,3-trichlorobenzene, 1,2,4-trichlorobenzene, iodobenzene, 1,2-diiodobenzene, 1,3-diiodobenzene, 1,4-diiodobenzene, 1,2,3-triiodobenzene, 1,2,4-triiodobenzene, toluene, fluoroform, Benzene, 2,3-difluorotoluene, 2,4-difluorotoluene, 2,5-difluorotoluene, 2,3,4-trifluorotoluene, 2,3,5-trifluorotoluene, chlorotoluene, 2,3-dichlorotoluene, 2,4-dichlorotoluene, 2,5-dichlorotoluene, 2,3,4-trichlorotoluene, 2,3,5-trichlorotoluene, iodotoluene, 2,3-diiodotoluene, 2,4-diiodotoluene, 2,5-diiodotoluene, 2,3,4-triiodotoluene, 2,3,5-triiodotoluene, xylene or a combination thereof.

[0077] The non-aqueous electrolyte may further include vinyl ethylene carbonate, vinylene carbonate, or an ethylene carbonate-based compound represented by Chemical Formula 2 as an additive to improve cycle life.

[0078] [Chemical formula 2]

[0079]

[0080] In Chemical Formula 2, R7 and R8 are the same or different and may each independently be hydrogen, halogen, cyano (CN), nitro (NO2) or C1~C5 fluoroalkyl, provided that at least one of R7 and R8 is halogen, cyano (CN), nitro (NO2) or C1~C5 fluoroalkyl, and R7 and R8 are not hydrogen at the same time.

[0081] Examples of ethylene carbonate compounds may include difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, fluoroethylene carbonate, etc. In the case of further using an additive to improve cycle life, the amount of the additive may be appropriately controlled within a suitable range.

[0082] The lithium salt dissolved in the non-aqueous organic solvent supplies lithium ions to the battery, enables the basic operation of the rechargeable lithium battery, and improves the transport of lithium ions between the positive electrode and the negative electrode. Examples of the lithium salt may include at least one carrier salt selected from the following: LiPF6, LiBF4, LiSbF6, LiAsF6, LiN(SO2C2F5)2, Li(CF3SO2)2N, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide: LiFSI), LiC4F9SO3, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (wherein x and y are natural numbers, for example, integers of about 1 to about 20), lithium difluoro(bis(oxalato)phosphate, LiCl, LiI, LiB(C2O4)2 (lithium bis(oxalato)borate: LiBOB) or lithium difluoro(oxalato)borate (LiDFOB). The concentration of the lithium salt may range from about 0.1 M to about 2.0 M. If the lithium salt is included in the above concentration range, the non-aqueous electrolyte may have excellent performance and lithium ion mobility due to optimal non-aqueous electrolyte conductivity and viscosity.

[0083] Depending on the type of rechargeable lithium battery, a separator may be provided between the positive electrode and the negative electrode. For example, the separator may use polyethylene, polypropylene, polyvinylidene fluoride or a multilayer thereof (the multilayer has two or more layers), and may be a mixed multilayer, for example, a polyethylene / polypropylene double-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, a polypropylene / polyethylene / polypropylene three-layer separator, etc.

[0084] The diaphragm may include a porous substrate and a coating layer comprising a ceramic on at least one surface of the porous substrate. The ceramic may include, for example, SiO2, Al2O3, Al(OH)3, AlO(OH), TiO2, BaTiO2, ZnO2, Mg(OH)2, MgO, Ti(OH)4, ZrO2, aluminum nitride, silicon carbide, boron nitride, or a combination thereof.

[0085] According to another embodiment, the diaphragm may be a composite porous diaphragm including a porous substrate and a functional layer on the porous substrate. The functional layer may have additional functions, for example, it may be at least one of a heat-resistant layer and an adhesive layer. The heat-resistant layer may include a heat-resistant resin and optionally a filler. The adhesive layer may include an adhesive resin and optionally a filler. The filler may be an organic filler, an inorganic filler, or a combination thereof. The heat-resistant resin and the adhesive resin may be any material that can be used for the diaphragm in the related art.

[0086] Rechargeable lithium batteries can be classified into, for example, lithium ion batteries, lithium ion polymer batteries, or lithium polymer batteries depending on the types of separators and non-aqueous electrolytes. Rechargeable lithium batteries can also be classified into, for example, cylindrical, prismatic, coin-type, or pouch-type batteries depending on their shapes, and block-type batteries or thin-film-type batteries depending on their sizes.

[0087] Figure 1 is an exploded perspective view of a rechargeable lithium battery according to an embodiment. Figure 1 As explained in , the rechargeable lithium battery according to one or more embodiments may be a prismatic battery. In another example, the rechargeable lithium battery according to one or more embodiments may include batteries of various shapes, such as a cylindrical battery, a pouch-type battery, and the like.

[0088] refer to Figure 1 , a rechargeable lithium battery 100 according to one or more embodiments may include: an electrode assembly 40 manufactured by winding a separator 30 disposed between a positive electrode 10 and a negative electrode 20; and a case 50 accommodating the electrode assembly 40. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with a non-aqueous electrolyte (not shown).

[0089] Hereinafter, examples and comparative examples are described. The following examples and comparative examples are provided to emphasize the features of one or more embodiments, but it will be understood that the examples and comparative examples are not to be construed as being limited to the scope of the embodiments, nor are the comparative examples to be construed as being outside the scope of the embodiments. Further, it will be understood that the embodiments are not limited to the specific details described in the examples and comparative examples.

[0090] (Example 1)

[0091] Polyvinylidene fluoride was added to an N-methylpyrrolidone solvent to prepare a non-conductive polymer liquid having a solid amount of 3.0 wt %.

[0092] The artificial graphite is immersed in a non-conductive polymer liquid and dried to prepare a negative electrode active material, wherein the non-conductive layer formed by drying the non-conductive polymer liquid is entirely (e.g., completely) coated on the entire surface of the artificial graphite. Here, the weight ratio of the artificial graphite to the non-conductive polymer is 99.2:0.8, and the thickness of the non-conductive layer is 3.0 nm.

[0093] 98.8 wt% of the negative active material and 1.2 wt% of polytetrafluoroethylene were dry mixed at 5000 rpm for 10 minutes. The mixture was extruded to prepare a sheet-type and self-standing negative active material layer. The negative active material layer was laminated on a copper foil current collector to prepare a negative electrode.

[0094] A half-cell was manufactured using a negative electrode, a lithium metal counter electrode, and a non-aqueous electrolyte. The non-aqueous electrolyte was obtained by adding fluoroethylene carbonate to a mixed solvent (the mixed solvent was obtained by dissolving 1M LiPF6 in ethylene carbonate, ethylmethyl carbonate, and dimethyl carbonate (volume ratio 2:1:7)), and the amount of fluoroethylene carbonate added was 3.5wt% based on the total weight of the mixed solvent.

[0095] (Example 2)

[0096] A negative electrode and a half cell were manufactured in substantially the same procedure as in Example 1, except that the weight ratio of artificial graphite and non-conductive polymer was changed to 99.5:0.5 to prepare a negative active material in which a non-conductive layer having a thickness of 2.8 nm was formed.

[0097] (Example 3)

[0098] A negative electrode and a half cell were manufactured in substantially the same procedure as in Example 1, except that the weight ratio of artificial graphite and non-conductive polymer was changed to 99.0:1.0 to prepare a negative active material in which a non-conductive layer having a thickness of 3.5 nm was formed.

[0099] (Example 4)

[0100] A negative electrode and a half cell were manufactured in substantially the same procedure as in Example 1, except that the weight ratio of artificial graphite and non-conductive polymer was changed to 98.0:2.0 to prepare a negative active material in which a non-conductive layer having a thickness of 10 nm was formed.

[0101] (Comparative Example 1)

[0102] 98.8 wt % of artificial graphite negative active material and 1.2 wt % of polytetrafluoroethylene were dry mixed at 5000 rpm for 10 minutes and the mixture was extruded to prepare a sheet-type and self-standing negative active material layer. The negative active material layer was laminated on a copper foil current collector to prepare a negative electrode.

[0103] A half-cell was manufactured using a negative electrode, a lithium metal counter electrode, and a non-aqueous electrolyte. The non-aqueous electrolyte was obtained by adding fluoroethylene carbonate to a mixed solvent (the mixed solvent was obtained by dissolving 1M LiPF6 in ethylene carbonate, ethylmethyl carbonate, and dimethyl carbonate (volume ratio 2:1:7)), and the amount of fluoroethylene carbonate added was 3.5wt% based on the total weight of the mixed solvent.

[0104] (Comparative Example 2)

[0105] 98.0wt% of artificial graphite negative active material, 0.8wt% of polyvinylidene fluoride and 1.2wt% of polytetrafluoroethylene were dry mixed at 5000rpm for 10 minutes, and the mixture was extruded to prepare a sheet-type and self-standing negative active material layer. The negative active material layer was laminated on a copper foil current collector to prepare a negative electrode.

[0106] A half-cell was manufactured using a negative electrode, a lithium metal counter electrode, and a non-aqueous electrolyte. The non-aqueous electrolyte was obtained by adding fluoroethylene carbonate to a mixed solvent (the mixed solvent was obtained by dissolving 1M LiPF6 in ethylene carbonate, ethylmethyl carbonate, and diethyl carbonate (volume ratio 2:1:7)), and the amount of fluoroethylene carbonate added was 3.5wt% based on the total weight of the mixed solvent.

[0107] (Comparative Example 3)

[0108] Polyvinylidene fluoride was used instead of polytetrafluoroethylene in the preparation of the negative electrode according to Comparative Example 1. As a result, the negative electrode could not be prepared.

[0109] (Comparative Example 4)

[0110] 98.8 wt% of artificial graphite negative electrode active material and 1.2 wt% of polytetrafluoroethylene were mixed in N-methylpyrrolidone solvent to prepare negative electrode active material layer slurry. The negative electrode active material layer slurry was coated on a copper foil current collector, dried and pressed. As a result, a negative electrode could not be prepared.

[0111] Experimental Example 1: Evaluation of thermal stability

[0112] Thermogravimetric analysis (TGA) and evolved gas analysis (EGA) of the negative electrode active material layer according to Comparative Example 2 were performed. Figure 2 Shown in.

[0113] The half-cells according to Examples 1 to 4 and Comparative Examples 1 and 2 were charged and discharged once at 0.1C. The negative electrode active material was separated and obtained from the battery cells that were charged and discharged, and then the TGA and EGA of the negative electrode active material were measured. The results of Example 1 and Comparative Examples 1 and 2 were respectively Figure 3 to Figure 5 Shown in.

[0114] TGA was performed under an argon atmosphere and by increasing the temperature from a room temperature of 25°C (i.e., ambient temperature) to 1000°C at a rate of increase of 10°C / min to measure thermal weight loss. EGA was performed under an argon atmosphere and by increasing the temperature from a room temperature of 25°C to 1000°C at a rate of increase of 10°C / min using EGA-MS (evolved gas analysis-mass spectrometry) to measure the molecular weight of the released gas.

[0115] As in Figure 3 As shown in Figure 2 Similarly, the negative active material of Example 1 also shows a large peak associated with polytetrafluoroethylene (PTFE) at 500°C to 600°C. The ratio of the height of the peak associated with polytetrafluoroethylene appearing at 500°C to 600°C to the height of the peak associated with polyvinylidene fluoride appearing at 400°C to 500°C is about 10:1. From these results, it can be seen that if polyvinylidene fluoride is substantially and completely coated on the surface of artificial graphite, polytetrafluoroethylene can be retained, and therefore, the consumption of polytetrafluoroethylene due to the reaction of polytetrafluoroethylene with lithium can be suppressed.

[0116] However, as in Figure 5 As shown in FIG, Comparative Example 2 (in which polytetrafluoroethylene and polyvinylidene fluoride are physically mixed with artificial graphite) shows a surprisingly small peak associated with polytetrafluoroethylene, which is consistent with Figure 2 (The results before formation charging and discharging) are different. Figure 5 The peaks associated with polytetrafluoroethylene shown in Figure 4 (Comparative Example 1 showing the use of only polytetrafluoroethylene after formation charge and discharge) is similar. From these results, it can be seen that if polyvinylidene fluoride is physically mixed with polytetrafluoroethylene, the reaction of polytetrafluoroethylene with lithium during charge and discharge cannot be suppressed.

[0117] Experimental Example 2: Evaluation of Initial Efficiency

[0118] The half cells according to Examples 1 to 4 and Comparative Examples 1 and 2 were charged and discharged once at 0.1 C. The charge capacity and discharge capacity were measured, and the initial efficiency (discharge capacity / charge capacity percentage) was calculated from these results. The results are shown in Table 1.

[0119] (Table 1)

[0120]

[0121]

[0122] As shown in Table 1, Examples 1 to 4 including negative active materials in which the surface of artificial graphite is coated with a polyvinylidene fluoride non-conductive layer show appropriate charge capacity and discharge capacity. Examples 1 to 4 show an initial efficiency (i.e., higher than 92%) superior to that of Comparative Example 1 using only polytetrafluoroethylene (i.e., without a polyvinylidene fluoride non-conductive layer) and Comparative Example 2 using a mixture of polyvinylidene fluoride and polytetrafluoroethylene (i.e., both showing an initial efficiency of less than 89%).

[0123] Experimental Example 3: Evaluation of charging and discharging characteristics

[0124] The half-cells according to Examples 1 to 4 and Comparative Examples 1 and 2 were charged and discharged once at 0.1C to evaluate the charge and discharge characteristics. The results of Example 1 and Comparative Examples 1 and 2 are shown in Table 1. Figure 6 Shown in.

[0125] As in Figure 6 As shown in , Example 1 does not show a peak due to a side reaction between polytetrafluoroethylene and lithium. However, Comparative Examples 1 and 2 show a peak due to a side reaction.

[0126] By way of summary and review, one or more embodiments provide a negative electrode for a rechargeable lithium battery showing excellent initial efficiency and electrochemical characteristics. Another embodiment provides a rechargeable lithium battery including the negative electrode.

[0127] Example embodiments have been disclosed herein, and although specific terms are employed, these terms are used and interpreted in a general and descriptive sense only, and not for purposes of limitation. In some cases, as will be apparent to one of ordinary skill in the art at the time of filing this application, features, characteristics, and / or elements described in conjunction with a particular embodiment may be used alone or in combination with features, characteristics, and / or elements described in conjunction with other embodiments, unless specifically indicated otherwise. Accordingly, those skilled in the art will appreciate that various changes in form and detail may be made without departing from the spirit and scope of the invention as set forth in the claims.

Claims

1. A negative electrode for a rechargeable lithium battery, the negative electrode comprising: Anode current collector; as well as A dry negative electrode active material layer, located on the negative electrode current collector, the dry negative electrode active material layer comprising: a negative electrode active material having a crystalline carbon core and a non-conductive layer coated on the surface of the crystalline carbon core; and polytetrafluoroethylene binder.

2. The negative electrode for a rechargeable lithium battery according to claim 1, wherein the non-conductive layer comprises a non-conductive polymer selected from polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer or a combination thereof.

3. The negative electrode for a rechargeable lithium battery according to claim 1, wherein the polytetrafluoroethylene binder comprises fibrillated polytetrafluoroethylene. 4 . The negative electrode for a rechargeable lithium battery according to claim 1 , wherein the non-conductive layer has a thickness of 1 nm to 10 nm. 5 . The negative electrode for a rechargeable lithium battery according to claim 1 , wherein an amount of the non-conductive layer is 0.1 wt % to 2.0 wt % based on 100 wt % of the negative active material. 6 . The negative electrode for a rechargeable lithium battery according to claim 1 , wherein the amount of the polytetrafluoroethylene binder is 0.5 wt % to 3.0 wt % based on 100 wt % of the dry negative active material layer. 7 . The negative electrode for a rechargeable lithium battery according to claim 1 , wherein the negative active material is prepared by coating a non-conductive polymer liquid containing a non-conductive polymer in a solvent on the crystalline carbon core and drying the non-conductive polymer liquid.

8. A rechargeable lithium battery comprising: The negative electrode according to any one of claims 1 to 7; Positive electrode; as well as Non-aqueous electrolyte.

9. The rechargeable lithium battery according to claim 8, wherein when the evolved gas analysis of the negative electrode is performed after the rechargeable lithium battery is subjected to formation charge and discharge, the height ratio of the peak associated with polytetrafluoroethylene appearing at 500° C. to 600° C. and the peak associated with the non-conductive polymer appearing at 400° C. to 500° C. of the rechargeable lithium battery is 2:1 to 20:

1.

10. The rechargeable lithium battery according to claim 8, wherein when an evolved gas analysis of the negative electrode is measured after the rechargeable lithium battery is subjected to formation charge and discharge, a height ratio of a peak associated with polytetrafluoroethylene appearing at 500° C. to 600° C. and a peak associated with a non-conductive polymer appearing at 400° C. to 500° C. of the rechargeable lithium battery is 5:1 to 20:

1.

11. A method of forming a negative electrode for a rechargeable lithium battery, the method comprising: forming a negative electrode current collector; as well as forming a dry negative electrode active material layer on the negative electrode current collector, wherein the dry negative electrode active material layer comprises: a negative electrode active material having a crystalline carbon core and a non-conductive layer coated on a surface of the crystalline carbon core; and polytetrafluoroethylene binder.

12. The method according to claim 11, wherein forming the negative electrode active material comprises: adding a non-conductive polymer to a solvent to form a non-conductive polymer liquid; coating the non-conductive polymer liquid on the crystalline carbon core; as well as The non-conductive polymer liquid on the crystalline carbon core is dried to form the negative active material.